Correction to: Validity of the Italian multiple sclerosis neuropsychological screening questionnaire - Migliore, Simone; Landi, Doriana; Proietti, Francesca; D’Aurizio, Giulia; Squitieri, Ferdinando; Mataluni, Giorgia; Nicoletti, Carolina Gabri; Curcio, Giuseppe; Marfia, Girolama Alessandra (Neurological sciences, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10072-021-05168-4